2015
DOI: 10.1007/s11010-015-2452-9
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin promotes osteogenic differentiation of human mesenchymal stem cells through JNK and p38 MAPK pathways

Abstract: Apigenin is a plant-derived flavonoid and has been reported to prevent bone loss in ovariectomized mice, but the role of apigenin on osteogenic differentiation of human mesenchymal stem cells (hMSCs) has not been reported. In the present study, the effect of apigenin on osteogenic differentiation of hMSCs was explored. Our results showed that apigenin treatment significantly increased alkaline phosphatase (ALP) activity and mineralization in hMSCs. RT-PCR revealed that apigenin markedly up-regulated the mRNA e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 41 publications
4
37
0
Order By: Relevance
“…Our data demonstrated that osteoblastic cells treatment with apigenin and luteolin at a concentration of 1  μ M significantly increased the transcriptional level of COL-I, OPN, and OCN (Figure 9(a)). Similar concentrations of these two compounds have been used, and our findings are in agreement with the other experiments [2628]. In a previous study, we reported that linarin extracted from FCI enhanced the osteoblast differentiation in MC3T3-E1 cells in a dose-dependent manner [11].…”
Section: Resultssupporting
confidence: 92%
“…Our data demonstrated that osteoblastic cells treatment with apigenin and luteolin at a concentration of 1  μ M significantly increased the transcriptional level of COL-I, OPN, and OCN (Figure 9(a)). Similar concentrations of these two compounds have been used, and our findings are in agreement with the other experiments [2628]. In a previous study, we reported that linarin extracted from FCI enhanced the osteoblast differentiation in MC3T3-E1 cells in a dose-dependent manner [11].…”
Section: Resultssupporting
confidence: 92%
“…34 It has been reported that the activation of JNK and p38 leads to Runx-2 and Osterix expression, and promotes MSCs osteogenesis. 35 In the present study, IL-7 significantly reduced the phosphorylated levels of JNK, ERK1/2, and p38, which indicated IL-7 inhibited osteogenic differentiation of PDLSCs possibly through inactivation of MAPK signaling pathway. It should be noted that there are some limitations in this study.…”
Section: Il-7 Inhibits Osteogenic Differentiation Of Pdlscssupporting
confidence: 63%
“…Moreover, JNK inhibition was found to prevent the neuronal differentiation of mouse embryonic stem cells [24]. The activities of JNK and p38 are required for the differentiation of MSCs to osteocytes [25]. …”
Section: Introductionmentioning
confidence: 99%